E-Learning: An Implementation for Arabic Learning During the Covid-19 Pandemic - Rosyadi, Faiq Ilham; Ilmi, Munaya Ulil (Departemen Pendidikan Bahasa Arab, 2021)
Arabic learning must be dynamic following the challenges of the times. The incompatibility between planning and implementing Arabic learning caused by the COVID-19 pandemic has made Arabic learning nonoptimal. This research is oriented to describe E-learning implementation for Arabic learning during the Covid-19 pandemic. This research is library research using a qualitative approach with a descriptive analysis method. The data collection technique in this study was carried out by exploring reference books and journals. The analysis technique uses an interactive data analysis model, which is carried out through data collection, data reduction, data explanation, and conclusions. Based on the results and discussion, it can be concluded that the use of e-learning in learning Arabic during the pandemic can be carried out following the learning implementation plan that has been prepared. This is because e-learning has features that teachers need in four Arabic language skills, namely: listening skills, speaking skills, reading skills, and writing skills.